Conjugative Transfer of the pVA1-Type Plasmid Carrying the pirABvp Genes Results in the Formation of New AHPND-Causing Vibrio - Dong, Xuan; Song, Jipeng; Chen, Jiayuan; Bi, Dexi; Wang, Wenchao; Ren, Yanbei; Wang, Hailiang; Wang, Guohao; Tang, Kathy F. J.; Wang, Xuepeng; Huang, Jie (Frontiers in Cellular and Infection Microbiology, 2019)
Acute hepatopancreatic necrosis disease (AHPND) has caused sharp declines in aquaculture industries of whiteleg shrimp Penaeus vannamei in Asia and the Americas since 2010. Vibrio parahaemolyticus, V. campbellii, V. owensii and V. punensis have been proved to cause AHPND. However, the mechanisms underlying the burgeoning number of Vibrio species that cause AHPND is not known. All of AHPND-causing Vibrio bacteria (VAHPND) harbor a highly homologous plasmid (designated as pVA1-type) carrying pirABvp toxin genes. In this study, we demonstrate conclusively that the pVA1-type plasmid can be transferred from VAHPND to non-pathogenic bacteria. We constructed a pVPGX1-Cmr plasmid (a pVA1-type plasmid) by adding a chloramphenicol resistance gene as a marker in a donor AHPND-causing V. parahaemolyticus 20130629002S01 (Vp2S01). Horizontal transfer of this plasmid was successfully performed from the AHPND-Vp2S01 to a non-pathogenic strain of V. campbellii at the transfer efficiency of 2.6 x 10-8 transconjugant/recipient, and DNase I treatment did not eliminate the transfer. The recipient V. campbellii acquired the pVA1-type plasmid and was shown to produce pirABvp RNA and proteins. Challenge studies using the transconjugant caused 100% mortality in exposed groups of P. vannamei. The challenged shrimp, infected with the transconjugant bacteria, showed typical gross signs and histological lesions of AHPND. This is the first report demonstrating the conjugative transfer of an AHPND pVA1-type plasmid. It provides timely information for explaining the increased species of AHPND-causing Vibrio bacteria and will be useful in the development of management strategies leading to the prevention and control of AHPND.